ANALISIS PROSES PENGELASAN REPLATING LAMBUNG KAPAL PADA KONDISI FLOATING TERHADAP NILAI KEKERASANNYA: PENGELASAN LAMBUNG KAPAL - Djumiati, Andri; Mochammad Karim Al Amin; Egi Yuliora; Nurul Atik Hamida; Puspita Khumairoh; Deby Ardianti; Sabila Fitri Afsari (Politeknik Negeri Batam, 2025)
Replating the ship’s hull is an essential repair process to ensure that a vessel remains operationally seaworthy. Replating welding can be performed under both docking and floating conditions. These differing conditions influence the cooling rate, which in turn can result in variations in hardness (HV). This study examines the effect of varying the distance from the waterline (30, 60, 100, and 130 mm) and water temperature (25°C, 28°C, 30°C, and 32°C) on the hardness values produced during welding under floating conditions.Each variation combination was tested using the Vickers method with three repetitions, and the reported HV values represent the average of those measurements. The results show that the highest hardness value under floating conditions reached 218.5 HV (30 mm, 25°C), while the lowest was 195.7 HV (130 mm, 32°C). All measured hardness values remained within the acceptable limits specified by BKI for low-carbon steel.This study demonstrates that the closer the weld groove is to the water surface and the lower the water temperature, the higher the resulting hardness due to increased cooling rates. The limitations of this study include the absence of microstructural data and the unavailability of individual measurement data for further statistical analysis.